1997
DOI: 10.1021/jp962946u
|View full text |Cite
|
Sign up to set email alerts
|

IR Spectroscopic Study of H2O2, HDO2, and D2O2 Isolated in Ar, Kr, and Xe Matrices

Abstract: The vibrational spectrum of hydrogen peroxide, released from an urea hydrogen peroxide adduct compound, is studied in Ar, Kr, and Xe matrices. The gaseous products of the thermal decomposition of urea hydrogen peroxide in an argon atmosphere are determined using a low-resolution fast scanning FTIR−gas analyzer. Upon the solid sample being warmed to temperatures of ∼90 °C, only hydrogen peroxide is detected, and above that, NH3 and HNCO are evolved due to the decomposition of urea. The hydrogen peroxide−rare ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
114
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(135 citation statements)
references
References 32 publications
21
114
0
Order By: Relevance
“…The reaction DO 2 + D leading to D 2 O 2 has an exothermicity of 3.7 eV, but D 2 O 2 is not detected in the gas phase during irradiation. Previous studies showed that H 2 O 2 (D 2 O 2 ) can easily decompose in H 2 O (D 2 O) on the wall of chamber19, meaning that the H 2 O (D 2 O) signal obtained is due to molecules bouncing on the wall. In our experimental configuration, the number of bounced molecules that are detected are less than 10% (see Ref.…”
Section: Resultsmentioning
confidence: 99%
“…The reaction DO 2 + D leading to D 2 O 2 has an exothermicity of 3.7 eV, but D 2 O 2 is not detected in the gas phase during irradiation. Previous studies showed that H 2 O 2 (D 2 O 2 ) can easily decompose in H 2 O (D 2 O) on the wall of chamber19, meaning that the H 2 O (D 2 O) signal obtained is due to molecules bouncing on the wall. In our experimental configuration, the number of bounced molecules that are detected are less than 10% (see Ref.…”
Section: Resultsmentioning
confidence: 99%
“…The band at 2855 cm −1 (3.503 µm) in Fig. 1, with a full width at half maximum (FWHM) of 74 cm −1 (0.09 µm), was identified with the ν 2 + ν 6 combination mode (also possibly 2ν 6 and 2ν 2 ) of H 2 O 2 (Lannon et al 1971, Pettersson et al 1997. The underlying, sloping continuum on which the H 2 O 2 feature sits in Fig.…”
Section: Methodsmentioning
confidence: 91%
“…Recently, there has been a report of success in growing H 2 O 2 in a vacuum by vapor deposition of gaseous H 2 O 2 from urea hydrogen peroxide in a vacuum. 12 We do not follow this method here since we have found that it is inefficient for producing pure solid-phase H 2 O 2 by vapor deposition. Instead, we explored the possibility of obtaining pure H 2 O 2 and its compound by distillation of an aqueous solution in a vacuum after it is deposited on the substrate, taking advantage of the higher sublimation rate of water than of hydrogen peroxide.…”
Section: Introductionmentioning
confidence: 99%